Production and reproductive performance of crossbred cattle in Coastal Maharashtra - B G Desai; R S Yadav; Shalu Kumar; R G Burte; A J Mayekar (Journal of Livestock Biodiversity, 2025)
The study was conducted to assess the production and reproductive efficiency of crossbred cattle (Dangi × Red Sindhi × Jersey). A total of 270 crossbred cattle were selected and their information regarding production and reproduction performances were collected from farm records maintained at Cattle Breeding Farm, Nileli, Dist. Sindhudurg, Maharashtra for a period of 15 years (1980 to 1994). Data representing 270 crossbred cattle from 657 total records of productive and reproductive performances for a period of 15 years (1980 to 1996) were analyzed to determine, Persistency Index (PI), Standard Lactation Milk Yield (SLMY), Peak Yield (PY), Days to Attain Peak Yield (DAPY), Wet Average (WA), Lactation Length (LL), Dry Period (DP), Service Period (SP), Gestation Period (GP) and Calving Interval (CI). The overall least squares mean of persistency index (162.65±0.83), standard lactation milk yield (1394.97±10.50), peak yield (8.61±0.05), days to attain peak yield (42.35±0.43), wet average (4.75±0.03), lactation length (302.01±1.58), dry period (81.77±1.65), service period (107.55±2.09), gestation period (279.14±0.30) and calving interval (387.58±2.18), respectively. Therefore, it may be concluded that crossbred cattle (Dangi × Red Sindhi × Jersey) cattle give optimum production and reproductive performance under coastal zone of Maharashtra.